Activation of the β-carbonic anhydrase from the protozoan pathogen Trichomonas vaginalis with amines and amino acids. (1st January 2021) - Angeli, Andrea; Urbański, Linda J.; Hytönen, Vesa P.; Parkkila, Seppo; Supuran, Claudiu T.
Abstract: We report the first activation study of the β-class carbonic anhydrase (CA, EC 4.2.1.1) encoded in the genome of the protozoan pathogen Trichomonas vaginalis, TvaCA1. Among 24 amino acid and amine activators investigated, derivatives incorporating a second carboxylic moiety, such as L-Asp, L- and D-Glu, were devoid of activating effects up to concentrations of 50 µM within the assay system, whereas the corresponding compounds with a CONH2 moiety, i.e. L-Gln and L-Asn showed modest activating effects, with activation constants in the range of 26.9 − 32.5 µM. Moderate activation was observed with L- and D-DOPA, histamine, dopamine, serotonin, (2-Aminoethyl)pyridine/piperazine and morpholine (KA 's ranging between 8.3 and 14.5 µM), while the best activators were L-and D-Trp, L-and D-Tyr and 4-amino-Phe, which showed KA 's ranging between 3.0 and 5.1 µM. Understanding in detail the activation mechanism of β-CAs may be relevant for the design of enzyme activity modulators with potential clinical significance.